Estimation of baseline emissions, forest reference emission level, and carbon removals due to forest area changes in Afghanistan between 1993 and 2030 - Narges Teimoory; Nophea Sasaki; Issei Abe (Cleaner Production Letters, 2022)
To benefit from reducing deforestation under the Paris Agreement, developing countries need to establish a forest reference emission level (FREL) but no FREL study exists in Afghanistan yet. This study is aim at determining the FREL for Afghanistan between 2020 and 2030 using the retrospective and prospective approaches. Data of forest area in 1993 and 2010 and a Tier-2 emission factor were used to obtain the baseline emissions in closed forest, open forest, undifferentiated open forest, and high shrubs. Carbon stocks in four carbon pools were considered. Loss of closed forest emitted approximately 7.2 TgCO2 year−1, while increase in areas of other forest categories resulted in carbon sequestration of approximately 2.6 TgCO2 year−1 between 1993 and 2010. Depending on the chosen approaches, FRELs in Afghanistan can range from 1.3 TgCO2 year−1 for retrospective approach to as high as 2.3 TgCO2 year−1 for prospective approach between 2020 and 2030. Enhancement of carbon stocks and reducing deforestation could achieve emission reductions amounting up to 36.4% of the total emissions in Afghanistan. This study was the first attempt to determine the national FREL in Afghanistan, paving the way for understanding the impacts of future development on deforestation and carbon emissions in this country.